Southern crossings : poetry, memory, and the transcultural south - Turner, Daniel Cross (University of Tennessee Press, 2012)
"Daniel Cross Turner has made a key contribution to the critical study and appreciation of the diverse field of contemporary Southern poetics. "Southern Crossings" crosses a gulf in contemporary poetry criticism while using the idea-or ideas, many and contrary-of "Southernness" to appraise poetries created from the profuse, tangled histories of the region. Turner's close readings are dynamic, even lyrical. He offers a new understanding of rhythm's central place in contemporary poetry while considering the work of fifteen poets. Through his focus on varied yet interwoven forms o.